2017
DOI: 10.1186/s40842-017-0044-1
|View full text |Cite
|
Sign up to set email alerts
|

Renin Angiotensin system-modifying therapies are associated with improved pulmonary health

Abstract: BackgroundPulmonary diseases are often complicated and have diverse etiologies. One common factor is the lack of therapeutics available for these diseases. The goal of this study was to investigate the impact of Renin-Angiotensin System (RAS)-modifying medications on incidence and time to pulmonary complications.MethodsA retrospective analysis was conducted using claims data from a US commercial insurance company (2007–2013). The study consisted of patients with an emerging hypertension (HTN) diagnosis. Cox an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 26 publications
0
23
0
2
Order By: Relevance
“…This also applies to viral pneumonia, in which RAS blockers have been associated with improved pneumonia-related outcomes. 23,24 Is hypertension associated with COVID-19 infections?…”
Section: Antihypertensive Treatment and Lrtismentioning
confidence: 99%
“…This also applies to viral pneumonia, in which RAS blockers have been associated with improved pneumonia-related outcomes. 23,24 Is hypertension associated with COVID-19 infections?…”
Section: Antihypertensive Treatment and Lrtismentioning
confidence: 99%
“…A recent pharmacoeconomic analysis of the effect of inhibitors of the pathological of RAS on pulmonary infections supporting the translatability of these results to diabetic patients. Using a deidentified insurance claims data set it was shown that even newly diagnosed T2DM is associated with higher incidence of pulmonary infections and that RAS-modifying drugs can reduce these outcomes (54). Future studies will explore mechanisms by which Mas agonism improves immune function in diabetic patients and the role of other immune cells in this paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective analysis of 215,225 American patients revealed that treatment with ACEIs or ARBs slowed the progression of pulmonary complications in COPD patients [76]. The analysis of the medical records of 182 ARDS patients showed an increased survival rate in patients treated with ACEIs or ARBs [77]. The Cox regression analysis of the data obtained in the longitudinal observational Fremantle Diabetes Study Phase II, found that the use of ACEIs/ARBs was associated with a reduced risk of pneumonia/influenza in patients with type 2 diabetes mellitus [78].…”
Section: Pharmacological Inhibition Of Ace and At1r In Pulmonary Disementioning
confidence: 99%